a+a+a+b+b=28,a+a+b+b+b=27,a=[ ],b=[
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 11:14:36
a+a+a+b+b=28,a+a+b+b+b=27,a=[],b=[a+a+a+b+b=28,a+a+b+b+b=27,a=[],b=[a+a+a+b+b=28,a+a+b+b+b=27,a=[],b
a+a+a+b+b=28,a+a+b+b+b=27,a=[ ],b=[
a+a+a+b+b=28,a+a+b+b+b=27,a=[ ],b=[
a+a+a+b+b=28,a+a+b+b+b=27,a=[ ],b=[
a+a+a+b+b=28得:3a+2b=28-------①
a+a+b+b+b=27得:2a+3b=27-------②
①×3-②×2,得:5a=30,所以:a=6
将a=6带入②,得:2×6+3b=27,得:b=5
答案:a=6,b=5
由题意得3a+2b=28 ①
2a+3b=27 ②
①×2得 6a+4b=56 ③
②×3得 6a+9b=81 ④
④-③得 5b=25
b=5
将b=5代入①得
3a+10=28
a=6
a=6 b=5
3a+2b=28。 2a+3b=27
则a-b=1
则a=6。 b=5
b=5,a=6
a+a+a+b+b=28,a+a+b+b+b=27,
3a+2b=28 2a+3b=27
两式相加得
5a+5b=55 2a+2b=22
a=6
b=5
a=[ ],b=[ ]
(a+b).(a-b)
a/b-b/a
a+b>a-b,
A-B=A/B
a-b>a,a+b
a+a+a+b+b=28,a+a+b+b+b=27,a=[ ],b=[
如果a+a+a+b+b=28,a+a+b+b+b=27,那么a=( ),b=( )
a=a+a+b+b=28,a+a+b+b+b=27,那么=【 】,b=[ ],a+a+a+b+b=28,a+a+b+b+b=27,,那么a=[ ],b=[ ],
-2a(a+b)+b(a+b)
化简|a|+|-b|-|a-b|-|a+b|
化简 |b|-|a|+|a-b|+|a+b|
[(a+b)(a-b)-(a-b)
(a+b)(a-b)-a-b因式分解
化简 |a-b|+|a+b|-|a-b|
因式分解 a(a+b)-b(a-b)
a(a+b)-b(a-b)
计算a+b/b-a-b/b
A*b/a>A ,那么a/b